2021
DOI: 10.1007/s40266-021-00861-7
|View full text |Cite
|
Sign up to set email alerts
|

MediQuit, an Electronic Deprescribing Tool for Patients on Polypharmacy: Results of a Feasibility Study in German General Practice

Abstract: Background Deprescribing is an important task for general practitioners (GPs) in the face of risky polypharmacy. The electronic tool "MediQuit" was developed to guide GPs and patients through a deprescribing consultation that entails a drug-selection phase, shared decision making, and advice on safe implementation. Objectives A pilot study was conducted to determine the target group of patients that is selected for consultation and to assess the impact, patient involvement, and feasibility of the tool. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(27 reference statements)
0
8
0
Order By: Relevance
“… 65 69 A pilot study among 16 general practitioners in Germany found that an electronic tool may assist in identifying deprescribing opportunities and promote patient involvement and shared decision making. 64 Our findings suggest that even among relatively healthy older adults polypharmacy is common, which makes this population also a target for deprescribing interventions.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“… 65 69 A pilot study among 16 general practitioners in Germany found that an electronic tool may assist in identifying deprescribing opportunities and promote patient involvement and shared decision making. 64 Our findings suggest that even among relatively healthy older adults polypharmacy is common, which makes this population also a target for deprescribing interventions.…”
Section: Discussionmentioning
confidence: 73%
“…In Portugal, an ongoing nationwide three-phase study on deprescribing is investigating barriers and facilitators of deprescribing perceived by older adults and their acceptance to have regular medications deprescribed 65 69. A pilot study among 16 general practitioners in Germany found that an electronic tool may assist in identifying deprescribing opportunities and promote patient involvement and shared decision making 64. Our findings suggest that even among relatively healthy older adults polypharmacy is common, which makes this population also a target for deprescribing interventions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Hence, it becomes imperative for a physician to examine patient approach on goals of therapy. It also takes into consideration the basic parameters of chronic conditions and medications and affords prime concern regarding prescription to slow down the disease progression along with minimizing the health decline [ 36 , 37 ]. It has been observed that only a limited percentage of the elderly community debate health-related decision-making priorities with their primary care physicians.…”
Section: Deprescribing Approachesmentioning
confidence: 99%
“…Here, patients and physicians review and assess the patients’ medication regimen and identify, weigh, and decide on opportunities for improvement. First evaluation of MQu by our team indicate satisfactory effectiveness with 70% of patients reporting drug discontinuation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%